Design Of Information Systems On Salesman Operational Based On Android at CV. Dwi Star - Tri Evania Sugito; Tan Amelia; Teguh Sutanto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
CV. Dwi Star is a company engaged in the field of importers of stationery, such as a stapler, perforator, cash box, stick note, display book, tape dispenser, glue, binders swing clip, calculator, and others. Stationery has various brands, such as Eagle, Phoenix, Pronto, Retype, Fastener, Bofa, Nashua, Pentel, and others. The goods were shipped from abroad, with prices following the dollar exchange rate, so that the sales price is uncertain (unstable). Is currently marketing the product on the company's CV. Dwi Star conducted by a salesman. Salesman has a dual role in his work, that salesman not only did the ordering of products but also offer the products, finding new customers, and collect debts.Salesman will going around in various area in Indonesia (except Papua). The process of roving salesman in one area takes one week to three weeks. In the process, salesmen will offer their products by bringing a catalog that contains information on products. The goods list (catalogs) are placed in a folder with the current total of about 49 sheets containing dozens of products types and kinds of this product does not include the same number but different product types, sizes, and colors. Salesman also perform the billing process to customers who still had debt. List of the bill will be created manually by the enterprise admin. Salesman collect the debt from the customer and the customer can pay off the debt in three ways, namely transfer, demand deposits, and cash. Confirmation of payment is only be completed by a salesman and a customer, and then salesmen will confirm it to the current company admin after the salesman back to the company. It creates opportunities to  cheat by the salesman.In connection with these problems, it is proposed Operational Information System Design Based Salesman Android that can be taken anywhere. Android-based operational applications salesman is devoted to help the salesman operational performance. The salesman operational applications provide useful product information to assist in the search speed of goods and prices thats up to date, can order the products, the addition of new customers, and displays a list of customer billing sent by e-mail to admin.